Conceptual development of a lightning protection system based on on-site evaluation (grounding system) - 414402 Siti Norhaslina Mohtar (Skudai : Universiti Teknologi Malaysia, 2004)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2004